2018
DOI: 10.13005/bpj/1500
|View full text |Cite
|
Sign up to set email alerts
|

Zingiber Officinale Alleviates Maternal and Fetal Hepatorenal Toxicity Induced by Prenatal Cadmium

Abstract: This study was designed to address the protective effects of Zingiber officinale on the toxic outcomes of prenatal Cadmium administration on pregnancy outcome. Pregnant female Sprague-Dawley rats were randomly divided into four groups (eight rats/each), control group received distilled water, 2nd group treated with 8.8 mg of CdCl2/kg b. wt, 3rd group treated with 250 mg of Zingiber officinale/kg b. wt, and 4th group treated with 250 mg of Zingiber officinale/kg b. wt, followed by 8.8 mg of CdCl2/kg b.wt. Daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Moreover, histopathological studies also revealed that the changes in the morphological structure of the tubules were more advanced at a higher level of exposure to Cd. Similar to those noted in the Cd 1 and Cd 5 groups, pathological changes in the histological structure of the kidney were also reported by other authors, however, at higher levels of exposure to this xenobiotic [33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, histopathological studies also revealed that the changes in the morphological structure of the tubules were more advanced at a higher level of exposure to Cd. Similar to those noted in the Cd 1 and Cd 5 groups, pathological changes in the histological structure of the kidney were also reported by other authors, however, at higher levels of exposure to this xenobiotic [33][34][35][36][37][38].…”
Section: Discussionsupporting
confidence: 89%
“…Although the toxic impact of Cd on the kidneys has been known for a long time and has been the subject of many studies, the mechanism of the nephrotoxic action of this xenobiotic, as well as the risk of this organ damage under low-level exposure, have not been sufficiently studied (for a review, see [2]). In the available literature, there are numerous studies on the damaging impact of Cd on the kidney conducted in laboratory animals; however, the used experimental models do not correspond to human exposure in terms of the dose (moderate, high, and even very high doses were administered) of this xenobiotic and the route of intoxication [33][34][35][36][37][38]40,[47][48][49]. To our knowledge, the experimental model we created is the only in vivo model constructed so far that well reflects human environmental exposure, and, therefore, we discuss our findings in the light of data from epidemiological studies.…”
Section: Discussionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: https: //www.mdpi.com/article/10.3390/ijms24098413/s1. References [5,17,22,37,66,72,84,126,146,149,[167][168][169][178][179][180][181][182][183][184][185][186][187][188][189][190][191] are cited in the supplementary materials.…”
Section: Supplementary Materialsmentioning
confidence: 99%